The role of Employing e-learning in integrating students with learning difficulties with ordinary students from the point of view of basic stage teachers in South Hebron Directorate - Amro, Feryal Abdulaziz; Al-Hamouri, Maryam Rafieq (Journal of Educational and Psychological Sciences, 2024)
This study aimed to identify the extent of e-learning integration for students with learning difficulties, its obstacles, and its significance. To achieve the research goal, a descriptive-analytical method was employed, utilizing a questionnaire consisting of 30 items across three axes. A simple random sample of 60 teachers was selected. The study’s results indicated that the overall role of e-learning in integrating students with learning difficulties with their peers was high. The extent of e-learning utilization for integrating these students was moderate, while the obstacles to e-learning integration were significant. The perceived importance of e-learning for integrating students with learning difficulties, from the perspective of elementary teachers, was high. No statistically significant differences were found in the averages of the role of e-learning integration due to study variables. The findings also revealed that the integration of students with learning difficulties using technology is moderate, with teachers facing a lack of resources and weak technical skills, yet recognizing that e-learning enhances student engagement and focus. Based on the results, the study recommended supporting teachers’ technical skills, providing modern educational devices, and organizing training programs to enhance the integration of students with learning difficulties. It also suggested upgrading school infrastructure and establishing local councils to gather community support for building modern schools and providing technical teams to support the use of technology in education.